LINGUISTYLISTICAL ANALYSIS OF ALLITERATION - Khurinisa Khudoyberdiyeva (The Conference Hub, 2025)
The article reveals the linguistic stylistic analyss of the phonostylistic units used in the poetry of the poet Khosiyat Rustamova, who has her own words and voice in modern Uzbek poetry.
Keywords: phonetics, stylistics, phonology, phonostylistics, alliteration, assonance, gemination.